2021
DOI: 10.21512/lc.v15i1.7165
|View full text |Cite
|
Sign up to set email alerts
|

English Language Teachers’ Perspective of Using L1 in TEFL Class

Abstract: The research discussed the using the first language in teaching a foreign language that had been a debate for language teaching practitioners for decades in language acquisition. The debate was about whether it was all right to use it in a foreign language class or not and how it affected the students’ learning process and result. Because of the pro and cons of using the first language in teaching a foreign language, the research was conducted to find out the use of the first language in teaching English as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Finally, despite the evidence above supporting L1 in the L2 classroom, we do not prescribe indiscriminate use of the L1, but judicious use of it. By that we mean, based on the studies that investigated the roles and functions of the L1 (Algazo, 2022;Clancy, 2018;Georgious & Krulatz, 2018;Hasrina, et al, 2018;İnal & Turhanlı, 2019;Mahmud, 2018;Perdani, 2021;Shariati, 2019;Taşçı & Aksu Ataç, 2020), using the learners' first language to teach grammar, to explain difficult vocabulary, to confirm meaning, to manage the classroom, to make students feel more comfortable, and in particular, to communicate with learners at lower levels of proficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, despite the evidence above supporting L1 in the L2 classroom, we do not prescribe indiscriminate use of the L1, but judicious use of it. By that we mean, based on the studies that investigated the roles and functions of the L1 (Algazo, 2022;Clancy, 2018;Georgious & Krulatz, 2018;Hasrina, et al, 2018;İnal & Turhanlı, 2019;Mahmud, 2018;Perdani, 2021;Shariati, 2019;Taşçı & Aksu Ataç, 2020), using the learners' first language to teach grammar, to explain difficult vocabulary, to confirm meaning, to manage the classroom, to make students feel more comfortable, and in particular, to communicate with learners at lower levels of proficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Algazo, (2022) and Taşçı and Ataç (2020) found that teachers mostly used the L1 at lower levels of proficiency. Likewise, Perdani's (2021) research showed that four high school English language teachers from Indonesia indicated through questionnaires and semi-structured interviews that they use the L1 because it was easier for them to interact with their students, explain L2 grammar, clarify meaning, and teach difficult words. From İnal and Turhanlı's (2019) questionnaires and semistructured interviews, 18 EFL university teachers from Turkey expressed they believe the L1 has several functions such as teaching grammar, explaining vocabulary, dealing with disciplinary issues, and raising students' awareness of the differences and similarities between English and their L1.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the perspectives of students and teachers on the usage of L1 in English teaching are relatively consistent. Researchers such as (Marsella, 2020;Perdani, 2021) revealed that learners' L1 utilized as a resource in the foreign language classroom to give explanations of confusing English topics, but its overuse resulted in overreliance, which was a less desired outcome.…”
Section: The Consistency Of Teachers' Views With the Student's Viewsmentioning
confidence: 99%